Pancreaticoduodenal resection with marginal resection of the portal vein: case study - Sergeevich, Belyuk Konstantin; Vladislavovich, Mahiliavets Edward; Wattaladeniya, Poorna Gayan; Priyadarshani, M. G. W. M. Varsha (International Surgery Journal, 2023)
Pancreatic cancer (PC) represents a challenging manifestation of a gastrointestinal tumour, which poses a formidable impediment for healthcare professionals and patients alike. The prognosis for this condition is often discouraging, particularly following a pancreatectomy, which has a poor five-year survival rate. The sole practical cure for PC is surgical resection, despite the negative outcomes. The standard surgical procedure for pancreatic head cancer is pancreaticoduodenectomy (PD). Although PD has been associated with higher morbidity and mortality rates, recent advancements have reduced the risks associated with this operation. When it comes to PC surgery, one promising approach is the resection of the portal vein. This technique has been shown to improve the ability to remove the cancerous tissue (resectability) and to remove it completely (radicality). This study was carried out at the department of pancreatology hepatology and transplantation of organs and tissues, Grodno regional clinical hospital in Grodno, Belarus. Our team treated a patient with pancreatic adenocarcinoma, who underwent a pancreaticoduodenal resection and marginal resection of the portal vein as part of their treatment plan. PD with marginal resection of the portal vein reduces risks and improves patient outcomes, as confirmed by CT and ultrasound data. Further research is needed to expand its efficacy and improve patients’ recovery and quality of life post-surgery.